2021
DOI: 10.21037/qims-20-626
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning reconstruction versus iterative reconstruction for cardiac CT angiography in a stroke imaging protocol: reduced radiation dose and improved image quality

Abstract: Background: To assess the radiation dose and image quality of cardiac computed tomography angiography (CCTA) in an acute stroke imaging protocol using a deep learning reconstruction (DLR) method compared to a hybrid iterative reconstruction algorithm.Methods: Retrospective analysis of 296 consecutive patients admitted to the emergency department for stroke suspicion. All patients underwent a stroke CT imaging protocol including a non-enhanced brain CT, a brain perfusion CT imaging if necessary, a CT angiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 23 publications
1
42
0
Order By: Relevance
“…However, many studies have shown that the potential dose reduction obtained with IR algorithms was limited to low contrast liver lesions and the outcomes found on phantoms overestimated the real dose reduction in patients (44)(45)(46). Nevertheless, the first patient studies published on pulmonary or cardiac CT angiography and chest and abdominal CT have also confirmed that AiCE improved both image quality and lesion detection as compared with AIDR 3D for a given dose level (22,25,26,30) or with a dose reduction (26,29,34,35). Singh et al found that the dose could be reduced by −84% between a standard protocol (CTDI vol : 13.0±4.4 mGy) with AIDR 3D and a low-dose protocol (CTDI vol : 2.1±0.8 mGy) with AiCE for the detection of the same abdominal lesions and an overall image quality scored acceptable for more than 95% of patients (34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, many studies have shown that the potential dose reduction obtained with IR algorithms was limited to low contrast liver lesions and the outcomes found on phantoms overestimated the real dose reduction in patients (44)(45)(46). Nevertheless, the first patient studies published on pulmonary or cardiac CT angiography and chest and abdominal CT have also confirmed that AiCE improved both image quality and lesion detection as compared with AIDR 3D for a given dose level (22,25,26,30) or with a dose reduction (26,29,34,35). Singh et al found that the dose could be reduced by −84% between a standard protocol (CTDI vol : 13.0±4.4 mGy) with AIDR 3D and a low-dose protocol (CTDI vol : 2.1±0.8 mGy) with AiCE for the detection of the same abdominal lesions and an overall image quality scored acceptable for more than 95% of patients (34).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the TrueFidelity DNN was trained with both patient and phantom data whereas it was trained only with patient data for AiCE. CT images obtained with these algorithms using denoising techniques showed suppressed noise with no change of noise texture or distortion of anatomical and pathological structures (19,(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the complex algorithms of this technique require more time for image reconstruction. Recent developments have introduced image reconstruction techniques based on deep-learning, allowing to reduce radiation exposure and improving image quality even more while maintaining significant noise reduction [ 33 , 34 ]. Regarding emergency diagnostics, time is one of the most relevant factors, and therefore, deep learning algorithms such as AiCE (Canon Medical Systems, Otawara, Japan) and TrueFidelity™ (GE Healthcare, Chicago, IL, USA) may have the potential to boost diagnostic quality and to reduce reconstruction time simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the TrueFidelity T M system is trained with high-dose filtered-back projection (FBP) images [12]. Several studies have utilized DLR in the abdominal, chest, and brain CT imaging and cardiopulmonary CTA and found better image quality than other image reconstruction algorithms [13][14][15][16][17][18]. No studies so far have investigated the application of AiCE to brain CTA protocols.…”
Section: Introductionmentioning
confidence: 99%